Respuesta :
If we write the quadratic equation in the vertex form, will be easy to find the vertex.
The vertex form of a quadratic function is:
y = a(x - h)² + k
Where the vertex is (h. k).
We have:
y=(x+2)(x-2)
y = x² - 4
Form this we conclude: a = 1, h = 0, k = -4. Then:
A/ The vertex of y is (0, -4)
Answer is -4
The vertex will be the y value when x is 0, since 0 is the average number of the roots of this quadratic.
Then, you get (0+2)(0-2)=2*-2=-4
The vertex will be the y value when x is 0, since 0 is the average number of the roots of this quadratic.
Then, you get (0+2)(0-2)=2*-2=-4